Filtration in cohesive soils: numerical approach - Schaefer, Robert; Sędziwy, Stanislaw (Computer Assisted Methods in Engineering and Science, 1999)
Paper presents a numerical method for solving the initial boundary-value problem for a certain quasilinear parabolic equation describing the low velocity filtration problem. The convergence of the method is proved.